2021
DOI: 10.1142/s0219649221500313
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sentiment Orientation in Open Innovation Communities: Empirical Evidence from a Business Analytics Community

Abstract: This study aims to investigate the influence of presentation and sentiment orientation of user-generated ideas and reviews on idea adoption in open innovation communities (OICs). Drawing on the social influence theory, this study develops a research model that divides idea components into informational and normative determinants. The sentiment orientation of the idea title, description, and associated reviews is determined using a lexicon-based sentiment analysis approach. The research model is empirically tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 80 publications
0
25
0
Order By: Relevance
“…Ardito, Antonio [5] found that users' preference for a review decreases or even disappears if the review title has no relevance to the content of the review, as there is no mere contact effect. Conversely, the higher the relevance of the review title to the content of the review, the higher the users' preference for a review [62]. Therefore, in this study, it is postulated that the higher the relevance of the title of the knowledge payment product to the product description, the more likely it is that users will prefer this knowledge product and stimulate their knowledge payment behavior.…”
Section: Information Quality Of Product Descriptionmentioning
confidence: 89%
“…Ardito, Antonio [5] found that users' preference for a review decreases or even disappears if the review title has no relevance to the content of the review, as there is no mere contact effect. Conversely, the higher the relevance of the review title to the content of the review, the higher the users' preference for a review [62]. Therefore, in this study, it is postulated that the higher the relevance of the title of the knowledge payment product to the product description, the more likely it is that users will prefer this knowledge product and stimulate their knowledge payment behavior.…”
Section: Information Quality Of Product Descriptionmentioning
confidence: 89%
“…Since open innovation communities (OICs) are characterized by openness and cooperation, the issue of value co-destruction, which refers to the situation where the inappropriate use of resources leads to a reduction in one party’s welfare [ 1 ], is inherent to these communities. While OICs has been viewed as a means for firms to leverage external resources, expand their knowledge base, and maintain competitiveness, recent research indicates that interactions between enterprises and users may result in value co-destruction rather than value co-creation [ 6 , 7 ]. Consequently, it has become imperative for businesses to explore the mechanisms underlying this phenomenon to optimize the benefits of open innovation while minimizing potential risks.…”
Section: Introductionmentioning
confidence: 99%
“…The mixed-ownership stock exchange is invested in businesses with common shares that can be traded on the public stock market only in limited circumstances. Mixed-ownership stock exchanges are established in countries such as the United Kingdom (London Stock Exchange) and the United States (New York Stock Exchange) [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%